FAKTOR-FAKTOR YANG MEMPENGARUHI NASABAH UNTUK MENGADOPSI TEKNOLOGI INTERNET BANKING DI KALIMANTAN BARAT - Angga Permadi Karpriana (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2019)
This research is aimed to examine what factors affect bank customers in adopting or using internet banking services in Indonesia. This study focuses on the variables of Enjoyment, Information on Online Banking (Info on Online Banking), Security and Confidentiality (Security & Privacy), Quality of Internet Connection (Quality of Internet), Attitudes Toward Use (Attitude Towards Using) and also two variables contained in the Technology Acceptance Model (TAM).